Dynamique de deux espèces arbustives de la toundra arctique en réponse aux changements climatiques et au broutement du caribou migrateur - Morrissette-Boileau, Clara (Université Laval, 2017)
Generalized shrub expansion has been observed over the circumpolar Arctic in response to climate change. This phenomenon is causing major alterations to the biotic and abiotic environments, a consequence of the increased shrub growth in height. We characterised tundra shrub species dynamics in response to climate change and migratory caribou browsing. To do so, we evaluated dominant erect shrub species dynamics and tested experimentally how shrub responds to these disturbances, using Betula glandulosa as model species. Our results show that shrub cover in Deception Bay is mainly driven by B. glandulosa, a species with increasing recruitment since early 2000s. However, it seems that this species’ vertical structure remains low which might not modify the biotic and abiotic environment normally associated with shrub expansion. We also showed experimentally that increase in shrub growth is a result of enhanced soil nitrogen fertility, a proxy of increase microbiological activity in response to global warming. Moreover, we demonstrated that caribou browsing has a negative cumulative effect on B. glandulosa growth. Thus, we showed in this study that shrub expansion is rather limited in Deception Bay and might be slowed down by the combined effects of harsh climatic conditions and herbivores. Moreover, our study stressed that herbivores must be taken into account when predicting vegetation change in the tundra. L’augmentation du couvert arbustif est observée de façon généralisée à l’échelle circumpolaire en réponse aux effets directs et indirects des changements climatiques. Celle-ci causerait d’importantes transformations des environnements biotique et abiotique, principalement en réponse à l’augmentation en hauteur des arbustes au port érigé. Nous avons caractérisé la dynamique des espèces arbustives de la toundra arctique en réponse aux changements climatiques et au broutement du caribou migrateur. Pour ce faire, nous avons établi la dynamique des espèces arbustives dominantes et évalué expérimentalement les ...